2011
DOI: 10.1186/1748-717x-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tumor hypoxia using a two-enzyme system for in vitro generation of oxygen deficiency

Abstract: BackgroundOxygen deficiency in tumor tissue is associated with a malign phenotype, characterized by high invasiveness, increased metastatic potential and poor prognosis. Hypoxia chambers are the established standard model for in vitro studies on tumor hypoxia. An enzymatic hypoxia system (GOX/CAT) based on the use of glucose oxidase (GOX) and catalase (CAT) that allows induction of stable hypoxia for in vitro approaches more rapidly and with less operating expense has been introduced recently. Aim of this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…However, no expression of LOX was detected (control group included); there is also a lack of literature for LOX expression with Molm14 cells or the sister Molm13 cell line. Nonetheless, similar data for both CA9 and LOX expression was reported by Askoxylakis et al where GOX and CAT were dissolved in culture media to generate hypoxia for culturing head and neck squamous carcinoma cells (Askoxylakis et al, 2011).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…However, no expression of LOX was detected (control group included); there is also a lack of literature for LOX expression with Molm14 cells or the sister Molm13 cell line. Nonetheless, similar data for both CA9 and LOX expression was reported by Askoxylakis et al where GOX and CAT were dissolved in culture media to generate hypoxia for culturing head and neck squamous carcinoma cells (Askoxylakis et al, 2011).…”
Section: Discussionsupporting
confidence: 61%
“…This was most likely attributed to the accumulation of cytotoxic byproduct, namely gluconic acid and H 2 O 2 . This is not a unique problem to our system as other GOX/CAT-induced hypoxia culture systems (e.g., soluble or membrane-bound enzyme) also exhibited decreased cytocompatibility after 24 hours of culture (Askoxylakis et al, 2011;Huang et al, 2013;Zitta et al, 2012). One potential solution for this drawback is to replace the GOX-immobilized hydrogel and the CAT supplemented media frequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this approach presents some critical limitations, mainly in regard to oxygen diffusion and equilibration. Studies have demonstrated that it requires more than three hours for the medium inside the culture plate to equilibrate to the gas outside of it [3]. Therefore, the longer time required for culture medium to reach equilibrium and the lack of ability to generate oxygen gradients greatly limits the scope of application for such chambers.`…”
Section: Introductionmentioning
confidence: 98%